Multi‐Walled Carbon Nanotubes Suspensions as Liquid Conductors: Electrical and Mechanical Network Interplay - Sergio Lago‐Garrido; Dominik S. Schmidt; María J. Martín‐Alfonso; Lola González‐García (Advanced Electronic Materials, 2025)
Abstract Soft‐adaptive electronics require both sensor and conductor materials. The key parameter for these materials is their mechanoelectrical properties. Liquid metals and solid conductive composites have been exploited in this application field, but both are limited by either their chemical stability or limited flexibility, respectively. Electrofluids are a novel approach toward soft electronic components. They are concentrated colloidal suspensions of conductive particles, in which dynamic contacts retain electrical conductivity under deformation, filling the gap between liquid metals and solid composites. Here, the mechanical and electrical network interplay of electrofluids is studied based on multi‐walled carbon nanotubes (MWCNTs) in glycerol. These networks arise at different filler concentrations, showing a different response to external deformations. It is found that electrical conductivity occurs without the presence of a rigid mechanical network, which allows MWCNT suspensions to be electrically conductive even under flow conditions. By performing rheoelectrical measurements, the study observed how the mechanical and electrical networks evolve with the applied deformation. The study demonstrates the applicability of electrofluids with tailored mechanoelectrical properties as soft electrical connectors.